CELAAN FISIK PADA FILM IMPERFECT KARYA ERNEST PRAKASA (KAJIAN MITOS KECANTIKAN NAOMI WOLF) - Kanaya Afflaha Nissa; Nuria Alfi Zahrah; Dona Aji Karunia Putra (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
The purpose of this research is to describe the forms of verbal body shaming found in the film "Imperfect" by Ernest Prakasa. The method used is qualitative. Data were collected through the method of listening, recording, and documentation by using a data card instrument, and tested for validity through triangulation of sources. This research shows that; 1) body shaming in the work environment requires women to look beautiful and attractive as a condition for obtaining a position as manager, 2) body shaming has eroded women's confidence because in culture, women will be considered to exist if they are beautiful, 3) body shaming in religion requires women to look beautiful based on the demands of society and the media, 4) body shaming weakens women's sexuality in making love, 5) body shaming of fat forces women to go on strict diets that are harmful to health, and 6) body shaming has made women make changes to their bodies by that hurts.